The Authority of the Constitutional Court as a Negative Legislator in Decision No. 135/PUU-XXII/2024: Constitutional Analysis and Its Implications for Indonesia’s Electoral System - Rizal Wahyudi; Gilang Rizki Aji Putra (UIN Jakarta, 2026)
This study examines the authority of the Mahkamah Konstitusi as a negative legislator in Decision No. 135/PUU-XXII/2024 and its implications for Indonesia’s electoral system. In principle, the Court functions as a negative legislator, whose role is limited to annulling unconstitutional norms without creating new legal norms. However, the decision separating national and local elections has generated significant debate regarding the boundaries of the Court’s authority. This research aims to analyze whether the Court, in this decision, remains within its role as a negative legislator or has shifted toward a positive legislator, as well as to assess the implications of such a shift on the electoral system. This study employs normative legal research using statutory, conceptual, and case approaches. The findings indicate that Decision No. 135/PUU-XXII/2024 reflects a tendency of the Court to formulate new legal norms, thereby suggesting a shift toward a positive legislator role. Nevertheless, this shift may be justified within the framework of constitutional interpretation, particularly in addressing legal gaps through judicial law-finding. The implications of this decision extend beyond electoral system design, affecting the principles of separation of powers and constitutional stability in Indonesia. Keywords: Constitutional Court, Negative Legislator, Positive Legislator, Electoral System, Constitutional Law